DESIGNS OF LAMELLA ROOF WITH WOODEN I-BEAMSAND NODES OF TUBULAR ELEMENTS (Collection of scientific works «Modern structures of metal and wood», 2020)
In the article, the authors investigate the issue of the use of wooden I-beams with steel tubular nodes in the designs of lamella roof. Wooden I-beams have been proven to be effective and now the are widely used in the construction of floors and coatings of simple shapes, however, the use  in curved and polygonal  structures is complicated due to the  lack of developed  nodes of their  connections.  In  the  article,  the  authors  give  a  possible  version  of  such  a  node,  examine  its stress-strain state in the work of a circular-mesh arch with a span of 12 meters. The  aim  of  the  work  is  to  develop  efficient  and  compact  nodes  of  the  wooden  I-beams connection working as a part of lamella roof, to study the stress-strain state (SSS) of the developed node, the impact of its application on the SSS of structural elements and the bearing capacity of all the structure. The closest to the node presented in the article is the cross node, which is used in a lamella roof of the Paselnik system (without the use of steel elements). The cross node contains three jambs, which are combined, while two oncoming jambs enter on both sides with their spikes in the through jamb socket. The use of wooden I-beams as elements of the lamella roof will significantly facilitate their design, and the use of light nodes will simplify the process of their construction. The span of the structure under consideration is 18 meters, the height in the lock is 3 meters. The lamella roof consists of identical rectilinear jambs of the I-wooden beam, connected at right angles and whose length is 1515 mm. The considered lamella roof is assembled from wooden I-beams made of OSB with a wall of the  following  sizes:  beam  height  120  mm;  belt  height  40  mm;  belt  width  90  mm;  OSB  wall thickness 10 mm. The  calculations  in  the  "ANSYS  WORKBENCH"  and  "LIRA-SAPR"  software  systems shows  that  the  introduction  into  the  calculation  of  the  elements  of  the  joints  (steel  pipes) significantly  affects  the  stress-strain  state  of  the  all  structure  due  to  not  only  an  increase  in geometric characteristics and bearing capacity in nodes, but also, possibly, due to the work of these elements as stiffeners, which reduce the deformation of wooden I-beams and take on the action of torque, due to the fact that they are sections of a closed loop. Due to this work, the voltage in the connecting elements is more than 10 times higher than in the wooden I-beams, which is acceptable and, moreover, allows you to more fully use the capabilities of the material from which they are made - steel.